2016
DOI: 10.1186/s40360-016-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of heat shock proteins on Mn-induced toxicity in Caenorhabditis elegans

Abstract: BackgroundAll living cells display a rapid molecular response to adverse environmental conditions, and the heat shock protein family reflects one such example. Hence, failing to activate heat shock proteins can impair the cellular response. In the present study, we evaluated whether the loss of different isoforms of heat shock protein (hsp) genes in Caenorhabditis elegans would affect their vulnerability to Manganese (Mn) toxicity.MethodsWe exposed wild type and selected hsp mutant worms to Mn (30 min) and nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Living cells upon confronting adverse environmental stimulator, physiological stressor and even bacterial infection, can exert a rapid molecular response to promote cell adaptation for survival. HSP family represents one such example 38 . HSPs are highly evolutionarily conserved molecular chaperones, which are ubiquitously found in subcellular compartments, cells, tissues, and give immediate responses during any stress, tissue damage, or bacterial infection 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Living cells upon confronting adverse environmental stimulator, physiological stressor and even bacterial infection, can exert a rapid molecular response to promote cell adaptation for survival. HSP family represents one such example 38 . HSPs are highly evolutionarily conserved molecular chaperones, which are ubiquitously found in subcellular compartments, cells, tissues, and give immediate responses during any stress, tissue damage, or bacterial infection 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from our lab and others have shown that C. elegans treatment with Mn at early life (Larva-1 stage, L1) induces DAergic neurodegeneration in L1, L4 and young adults (Settivari et al , 2009; Benedetto et al , 2010; Settivari et al , 2013; Leyva-Illades et al , 2014; Avila et al , 2016; Ijomone et al , 2016). Additionally, treatment of L1 worms with Mn altered neurobehavioral parameters at a later stage.…”
Section: Neurodevelopmental Toxicity Studies In C Elegansmentioning
confidence: 92%
“…Similarly to higher organisms, in worms Mn has been reported to trigger reactive oxygen species (ROS) generation and induced oxidative stress (Settivari et al , 2009; Benedetto et al , 2010; Settivari et al , 2013; Avila et al , 2016), as well as alter activities of apoptotic proteins (Settivari et al , 2013) and PD-associated genes (Chen et al , 2015b). Expression of GST-1 (glutathione transferase 1) and SKN-1, a homologue of human nuclear factor (erythroid-derived 2)-like 2, NRF-2 – a transcription factor regulating antioxidant response involved in antioxidant and detoxification enzymes regulation, has been shown to inhibit Mn-induced developmental neurotoxicity in C. elegans (Settivari et al , 2009; Benedetto et al , 2010; Settivari et al , 2013).…”
Section: Neurodevelopmental Toxicity Studies In C Elegansmentioning
confidence: 99%
“…However, once ROS levels pass the required threshold, the defense against oxidative stress decreases, leading to toxicity. The activation of hsp-70 transcription suggests protection against protein oxidation and neuronal damage [ 117 ], which suggests that these chemicals play a role in oxidative damage.…”
Section: Discussionmentioning
confidence: 99%